2018
DOI: 10.1016/j.postharvbio.2018.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Induced accumulation of individual carotenoids and quality changes in tomato fruits treated with pulsed electric fields and stored at different post-treatments temperatures

Abstract: Està subjecte a una llicència de Reconeixement-NoComercial-SenseObraDerivada 3.0 de Creative Commons 1 Induced accumulation of individual carotenoids and quality changes in tomato fruits treated with pulsed electric fields and stored at different post-treatments temperatures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Recently, PEF is being applied as a pretreatment to induce the secondary metabolism in fruit and vegetables as well as to enhance different industrial processes such as drying, freezing, and frying. For instance, López-Gámez et al (2020) and González-Casado et al (2018) reported an increment in the concentration of carotenoids in carrots and tomatoes treated by PEF after 24 h of storage. Whereas Traffano-Schiffo et al (2017) observed that PEF increased the dehydration rate of kiwifruit by electrolytes' loss, and Tylewicz et al (2016) reported an improvement in the storage stability of freeze-dried apples pretreated by PEF.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, PEF is being applied as a pretreatment to induce the secondary metabolism in fruit and vegetables as well as to enhance different industrial processes such as drying, freezing, and frying. For instance, López-Gámez et al (2020) and González-Casado et al (2018) reported an increment in the concentration of carotenoids in carrots and tomatoes treated by PEF after 24 h of storage. Whereas Traffano-Schiffo et al (2017) observed that PEF increased the dehydration rate of kiwifruit by electrolytes' loss, and Tylewicz et al (2016) reported an improvement in the storage stability of freeze-dried apples pretreated by PEF.…”
Section: Introductionmentioning
confidence: 99%
“…Several commercial sensors are available to measure soil water content accurately, but analyzing and processing the data is time-consuming, often resulting in water stress between the measurement and the irrigation triggering as watering is usually not activated automatically in real-time [20]. The increased demand for healthy foods provides an opportunity to use such technologies and obtain products with enhanced nutritional properties [21].…”
Section: Introductionmentioning
confidence: 99%
“…Statistical analysis showed that electric field strength (ηp 2 = 0.437; p = 0.006), number of pulses (ηp 2 = 0.335; p = 0.025) and their interaction (ηp 2 = 0.493; p = 0.012) exerted a significant effect on the BI of vascular tissues, whereas cortical BI was mainly affected by electric field strength applied (ηp 2 = 0.679; p < 0.001). Some authors have reported browning increase after submitting products to PEF (González-Casado et al, 2018b;Ribas-Agustí et al, 2019) and they attributed these changes to cell membrane disruption and greater contact between released phenolic substances and their oxidative enzymes (e.g. polyphenol oxidase (PPO), peroxidase (POD)).…”
Section: Carrot Quality-related Parameters and Their Correlation With...mentioning
confidence: 99%
“…Apart from improving the extraction of bioactive compounds, PEF has been recently proposed as a tool to induce stress in plant products or cell cultures, thus stimulating the biosynthesis of bioactive compounds (Jacobo-Velázquez et al, 2017). Some studies have shown that PEF may cause the accumulation of flavonoids and flavan-3-oles in apples (Ribas-Agustí et al, 2019;Soliva-Fortuny et al, 2017), phenolic compounds in grapes (Balaša, 2014) and carrots (López-Gámez et al, 2020a) or carotenoids in tomato (González-Casado et al, 2018b;Vallverdú-Queralt et al, 2013). However, free radical generation during PEF treatment would also be involved in the oxidative degradation of some nutrients (Gianpiero .…”
Section: Introductionmentioning
confidence: 99%